Radiation exposure of microorganisms living in radioactive mineral springs - Kolovi, Sofia (HNPS Advances in Nuclear Physics, 2022)
The TIRAMISU collaboration gathers expertise from biologists, physicists, radiochemists and geologists within the Zone-Atelier Territoires Uranifères (ZATU) in France to study the response of microorganisms living in naturally radioactive mineral springs. Mineral springs are isolated ecosystems, extremely stable over geological time scales, which display different physicochemical and radiological parameters compared to their surroundings. Water and sediment samples collected in 27 mineral springs of the volcanic Auvergne region (Massif Central, France) have been analyzed for their microbial biodiversity and radionuclide content. Among the microorganisms present, diatoms (a microalgae species), widely used as environmental bioindicators of water quality, have shown to display an exceptional abundance of teratogenic forms in the most radioactive springs studied (radon activity up to 3700 Bq/L). The current work presents a first assessment of the dose received by the diatoms inhabiting naturally radioactive mineral springs. The radiological risk for microorganisms living in freshwater environments was estimated using the ERICA tool. Most of the sampled mineral springs were highly above the risk threshold of 10 mGy/h due to the large concentrations of radium in the sediments (up to 50 Bq/g). The complete radiological data on water and sediments are used as inputs to Monte Carlo simulations at micro- (GATE) and nano- (Geant4-DNA) scale in order to assess the direct and indirect damages on the diatom DNA.